HOMESCHOOLING ISLAMI MELAWAN ARUS PENDIDIKAN MAINSTREAM - Rizki Ramadan (NIHAYAH: Journal of Islamic Studies, 2025)
This article explores Islamic homeschooling as a form of resistance to the dominance of mainstream education in Indonesia. In recent years, there has been a significant increase in the adoption of Islamic-based homeschooling among urban and rural Muslim families. This shift is driven by dissatisfaction with the formal education system, which is often seen as overly secular, standardized, and lacking in spiritual integration. Using a qualitative approach, the study conducted case analyses of ten families practicing Islamic homeschooling in various cities, supported by in-depth interviews and document analysis of curricula and teaching materials. Findings indicate that learning models in Islamic homeschooling are highly creative and contextual, integrating Qur’anic memorization with real-life Islamic projects and curricula tailored to children’s innate disposition (fitrah). Despite challenges such as limited facilities and concerns over socialization, practitioners employ alternative strategies including learning communities and collaborative activities. The article highlights the concept of "Islamic Merdeka Belajar," aiming for holistic education that balances worldly knowledge and spiritual development. Looking ahead, Islamic homeschooling holds great potential to evolve into a hybrid model that collaborates with formal institutions. These findings call for regulatory support and systemic facilitation from the state to legitimize Islamic homeschooling as a vital part of national educational transformation one that is inclusive, value-based, and character-oriented.